Morphophysiogenetic characterization of wild poinsettia biotypes with low resistance to glyphosate - Agostinetto, Dirceu; Ulguim, André da Rosa; Vargas, Leandro; Silva, Jessica Dias Gomes da; Langaro, Ana Claudia (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to compare wild poinsettia (Euphorbia heterophylla) biotypes as to their morphological characteristics, as well as to determine their genetic similarity in the state of Rio Grande do Sul, Brazil, and to confront the light compensation point of susceptible biotypes and of biotypes with low-resistance level to glyphosate. Besides the morphology analysis, the study included the genetic characterization, by AFLP, of susceptible (GR50 = 58.65 g ha-1 a.e.) biotypes and of biotypes with low resistance (GR50 = 310.36 g ha-1 a.e.) to glyphosate. The competitive ability of the biotypes was inferred according to their light compensation point. The observed morphological characteristics do not allow to differentiate biotypes as to their geographical location, or their resistance level to glyphosate. The genetic analysis identified low genetic diversity among the 15 tested biotypes, with a large amount of subgroups. The biotypes with low resistance formed an isolated group. The susceptible biotypes showed the lowest values of light compensation point and, possibly, they have a greater competitive ability under low-luminosity conditions. The evaluated characteristics do not enable to differentiate genotypes with different levels of glyphosate resistance.